Metabolomic analyses reveal that graphene oxide alleviates nicosulfuron toxicity in sweet corn - Wang, Jian; Wang, Yanbing; Wang, Yanli; Zhong, Xuemei; Wang, Xiuping; Lin, Xiaohu (Frontiers in Plant Science, 2025)
Nicosulfuron can repress the growth and quality of sweet corn (Zea mays), and graphene oxide has been used for sustainable agriculture. However, the underlying mechanism of the toxicity of nicosulfuron that is mediated in sweet corn remains elusive. To explore the potential mechanism of GO-mediated nicosulfuron toxicity in sweet corn in this study, we investigated the effects of graphene oxide on nicosulfuron stress in the sweet corn sister inbred lines of H01 and H20. Furthermore, we performed a metabolomics analysis for the H01 and H20 under different treatments. The results showed that nicosulfuron severely affected the rate of survival, physiological parameters, photosynthetic indicators, and chlorophyll fluorescence parameters of corn seedlings, whereas foliar spraying with graphene oxide promoted the rate of survival under nicosulfuron toxicity. The metabolomics analysis showed that 70 and 90 metabolites differentially accumulated in the H01 and H20 inbred lines under nicosulfuron treatment, respectively. Graphene oxide restored 59 metabolites in the H01 seedlings and 56 metabolites to normal levels in the H20 seedlings, thereby promoting the rate of survival of the sweet corn seedlings. Compared with nicosulfuron treatment alone, graphene oxide resulted in 108 and 66 differential metabolites in the H01 and H20 inbred lines, respectively. A correlation analysis revealed that metabolites, such as doronine and (R)-2-hydroxy-2-hydroxylase-1,4-benzoxazin-3(4-hydroxylase)-1, were significantly correlated with the rate of survival, photosynthetic parameters and chlorophyll fluorescence parameters. Furthermore, metabolites related to the detoxification of graphene oxide were enriched in the flavonoid metabolic pathways. These results collectively indicate that graphene oxide can be used as a regulator of corn growth and provide insights into their use to improve crops in areas that are contaminated with nicosulfuron.